KONSEP PERNIKAHAN DALAM ISLAM (Studi Fenomenologis Penundaan Pernikahan Di Masa Pandemi) - Widiyanto, Hari (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2020)
This study aims to determine the concept of marriage in Islam in terms of phenomenological postponement of marriage due to the COVID-19 pandemic, although the law of origin of marriage is sunnah, but when an outbreak occurs in an area, delaying marriage is a noble thing because it complies with government regulations. The purpose of this study was to determine the concept of marriage in Islam and postponement of marriage in Islam due to a pandemic. This study used qualitative methods as well. The data collection process considered the availability of data in the library (Library Research). The data analysis technique used in this study is the content analysis technique. The results of this study are that delaying marriage due to the covid 19 outbreak is a form of interception which, if it continues to be carried out, will have an impact on the spread of the virus. It is also planned to be a very noble decision, because in addition to obeying the government it also helps protect others by reducing the spread of the Covid-19 outbreak because complying with government regulations is mandatory